2009
DOI: 10.1016/j.ajic.2008.08.007
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the anticipated emotional and behavioral responses to an avian flu outbreak

Abstract: Emotional responses may be important in predicting behavior after an outbreak of avian flu, and personal characteristics may predict both emotional and behavioral responses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
24
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 27 publications
5
24
0
Order By: Relevance
“…Our findings also suggest dependencies among negative affect, perceived risk, and avoidance behavior. Previous research has shown that perceived risk is a function of negative emotion and negative emotion may lead to greater avoidance behavior . In our study, we confirmed the effects of negative affect on both risk perception and behavioral intention individually, but found that the effect of negative affect on avoidance behavior could be fully mediated by risk perception.…”
Section: Discussionsupporting
confidence: 86%
“…Our findings also suggest dependencies among negative affect, perceived risk, and avoidance behavior. Previous research has shown that perceived risk is a function of negative emotion and negative emotion may lead to greater avoidance behavior . In our study, we confirmed the effects of negative affect on both risk perception and behavioral intention individually, but found that the effect of negative affect on avoidance behavior could be fully mediated by risk perception.…”
Section: Discussionsupporting
confidence: 86%
“…( 29‐31 ) Other studies have looked at perceived risk and behavior change in response to disasters. ( 32‐34 ) In this study, each video introduced respondents to new and developing information about an escalating flu epidemic. The recording of respondent responses following each video allowed for the dynamics of reactions to be captured over the episodes.…”
Section: Discussionmentioning
confidence: 99%
“… Sources : Bults et al ., Cowling et al ., Del Valle et al ., Kok et al ., Sadique et al ., and Smith et al …”
Section: Modeling Approaches For Individual Impact Categoriesmentioning
confidence: 99%